Biomechanics of Gait during Pregnancy: a review - Branco, Marco A. C. (2015)
European Union, QREN-InAlentejo-Programa Operacional do Alentejo, 2007–2013/National Strategic Reference Framework, project title Parque de Ciência e Tecnologia do Alentejo, Laboratório de Investigação em Desporto e Saúde/Alentejo’s Science and Technology Park, Sport and Health Research Center, Instituto Politécnico de Santarém, Escola Superior de Desporto de Rio Maior/Escola Superior de Saúde de Santarém/Polytechnic Institute of Santarém, and Sport Sciences School of Rio Maior/Health School of Santarém. Project coordinator is Rita Santos-Rocha (Project reference: ALENT-07-0262-FEDER-001883)